Household Level and Individual Antecedents of Employment Status in Malawi - Dunga, Hannah Mayamiko (Acta Universitatis Danubius. Œconomica, 2022)
In the face of high levels of poverty and unemployment, there is need to dissect and turn upside down any possible explanations that can assist in discovering a working formula. The most recent data collected by statistics office of Malawi, has information on the employment status of individuals and some important social economic characteristics. This paper uses the data to uncover the socioeconomic and household level antecedents of employment status of individual using the individual set of data. The main variables used were age, gender, literacy, religion, disability, and education level to properly profile the nature of individuals that are employed, to see if this is an issue of the supply side of the labour force or the demand side of labour from the industry. An understanding of this dynamic can go a long way in finding lasting solutions to the unemployment questions and subsequently the poverty question. The study used descriptive analysis, cross tabulation, and a binary logistic regression model to analyse the data. The results showed that males had a higher chance of getting employment as compared to the counterpart women, being literate also had a higher chance of getting employment than those who were illiterate. Age of an individual showed that older people up to a certain age had a better chance of getting employed than the younger generation and on education level, those with at-least some form of education had a better chance of being employed than those without, the disabled had a lower chance of getting employed than those not disabled. Lastly the study recommended policy makers to emphasise on the policy of increase in school attendance across gender to improve the literacy levels in the country and the level of education. Policies on gender discrimination in workplaces should also be emphasised. Government should introduce and increase the number of incubators of SMMEs to enhance entrepreneurship in the country which later may have.